Numerical Simulation and Performance Analysis of Twin Screw Air Compressors - W. S. Lee; R. H. Ma; S. L. Chen; W. F. Wu; H. W. Hsia (International Journal of Rotating Machinery)
A theoretical model is proposed in this paper in order to study the performance of oil-less and oil-injected twin screw air compressors. Based on this model, a computer simulation program is developed and the effects of different design parameters including rotor profile, geometric clearance, oil-injected angle, oil temperature, oil flow rate, built-in volume ratio and other operation conditions on the performance of twin screw air compressors are investigated. The simulation program gives us output variables such as specific power, compression ratio, compression efficiency, volumetric efficiency, and discharge temperature. Some of the above results are then compared with experimentally measured data and good agreement is found between the simulation results and the measured data.